PENGETAHUAN GURU FISIKA TENTANG PENGELOLAAN LABORATORIUM FISIKA DI SMP DAN SMA NEGERI KOTA BENGKULU - Cariti Dassa Urra (Jurnal Perspektif Pendidikan, 2019)
This study aims to describe the knowledge of physics teachers about the management of physics laboratories in SMP and SMA Negeri Bengkulu City. This ex-post facto descriptive study used a sample taken with a total sampling method to all physics teachers in SMP and SMA Negeri Bengkulu City. Data were collected using test instruments. The results of this study indicate that the junior high school physics teacher's knowledge about laboratory management is in the sufficient category indicated by the frequency of 35 respondents (64.8%) and the high school physics teacher's knowledge about laboratory management is also in the sufficient category indicated by the frequency of 22 respondents (84.6%). ). Knowledge based on teaching status, either not certified or certified or knowledge based on teaching experience, is in the sufficient category. Meanwhile, knowledge based on the aspects of factual knowledge, conceptual knowledge, procedural knowledge, and metacognition knowledge, the majority of respondents were in the sufficient category. The conclusion from this research is that the knowledge of physics teachers about physics laboratory management in SMP and SMA Negeri Bengkulu city is sufficient.